PENGARUH PENDEKATAN KETERAMPILAN PROSES TERHADAP KEMAMPUAN MELAKUKAN PRAKTIKUM IPA DI SD PADA MAHASISWA PGSD UNIVERSITAS TERBUKA - Noviana Desiningrum; Endang Nuryasana (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2018)
This research approach the process in lectures Practical skills in elementary school science. This study aims to determine the effect on the ability of the process skills approach doing practical science in primary schools. The research was conducted on students PGSD Open University in Surabaya, the odd semester of 2016-2017.This study is a quasi-experimental research, with pretest and posttest design. The results showed that: (1) activities with the faculty to manage learning process skills approach has very good category with a mean score of 4.03. (2) the learning activities of students in the learning process skills approach has a positive category with a mean score of 3.801. (3) Complete classical learning of 94.07% with a minimum completeness criteria of 75, (4) Students are motivated to learn by 89.62%. The results of data analysis with pretest and posttest design, for the parameters mean pretest and posttest mean shows that the skills approach effect on student learning outcomes, with a probability of 0.008.